Strategi Guru dalam Pelaksanaan Pembelajaran Luring (Luar Jaringan) di RA Ahsanil Hasna - Tika Budi Utami; Arlina Arlina; Sri Wahyuni (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2025)
This research aims to find out: (1) What strategies do teachers use in implementing offline learning at RA Ahsanil Hasna (2) What strategies do teachers use in implementing offline learning at RA Ahsanil Hasna (3) Why are these strategies used in implementing offline learning at RA Ahsanil Hasna. This research is qualitative research using a phenomenological approach, with research subjects: School Principals, Teachers and Students. In collecting data, researchers used interview, observation and documentation methods. The research results can be concluded: (1) The strategy used during the pandemic at RA Ahsanil Hasna was, expository strategy, where in this strategy, the teacher was the main source and provider of information. (2) Implementation of learning using the shift method is divided into 2 learning waves. This was obtained based on interviews with school principals and teachers at RA Ahsanil Hasna (3) The use of the shift method in offline learning activities at RA Ahsanil Hasna is more effective than learning via Whatsapp .